(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article will focus on Uzbekistan and the world transport network. The author, relying on archival data, analyzed the problem based on the available scientific literature and studied the specifics of Uzbekistan and the world transport network.